Analysis of the influence of workload and the quality of the nurse with the quality of medical services in the inpatient building B general hospital Royal Prima Medan 2019 - Rahma, Maulida; Khu, Adrian; Girsang, Ermi; Silalahi, Marlinang (International Journal of Research in Medical Sciences, 2021)
Background: Workload and quality of peer care has an important role in improving the quality of medical services in terms of patient satisfaction in hospital services, especially in the inpatient room. RSU. Royal Prima is a private type B hospital with a BOR of 87% based on the high number of patient visits in the inpatient room. The aim of the study was to determine the analysis of the influence of the workload and the quality of medical services in the inpatient building B RSU, Royal Prima Medan 2019. Methods: This type of quantitative research with a correlation study research design. On the workload of nurses with a total sampling technique of 148 nurses. On the quality of nurses using a purposive sampling technique, a sample of 148 people was taken from one month's patient population. Results: The results of this study on nurse workload from the measurement results based on the chi square test nurses workload has a statistically significant effect on the quality of medical services (p=0.005) and the quality of nurses has no influence on the quality of being able (p=0.950). Based on logistic regression odds ratio 1.025, which means nurses with light workloads will improve the quality of service 1.0 times compared to nurses with heavy workloads. Conclusions: It was concluded that the heavy workload can affect the quality of inpatient services marked by the number of patients not proportional to the number of nurses so it is necessary to increase the number of nursing human resources in the inpatient room of B building at RS, Royal Prima Medan in 2019.